2021
DOI: 10.1001/jamacardio.2020.7434
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical and Echocardiographic Outcomes in Young and Middle-aged Adults Undergoing the Ross Procedure

Abstract: IMPORTANCEThere is no ideal valve substitute for young adults requiring aortic valve replacement. Multicenter data supporting use of the Ross procedure with respect to long-term postoperative valve-related mortality and reintervention, as well as function of the autograft and pulmonary homograft, are needed.OBJECTIVE To determine the long-term clinical and echocardiographic outcomes in young and middle-aged patients undergoing the Ross procedure. DESIGN, SETTING, AND PARTICIPANTSA retrospective multicenter int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…[53][54][55] In this scenario, the Ross procedure has triggered a new wave of enthusiasm over the last decades. [56][57][58][59] Starnes et al 56 studied outcomes of two cohorts of adults (aged ≥18 years) with bicuspid aortic valves undergoing the Ross procedure. Mortality rates at 1, 5, and 10 years, respectively, was 2.8%, 2.8%, and 4.4% in the first cohort and 0%, 0%, and 0% in the second cohort.…”
Section: Ross Procedure-the Revival Of Interest In An Old Procedures ...mentioning
confidence: 99%
See 2 more Smart Citations
“…[53][54][55] In this scenario, the Ross procedure has triggered a new wave of enthusiasm over the last decades. [56][57][58][59] Starnes et al 56 studied outcomes of two cohorts of adults (aged ≥18 years) with bicuspid aortic valves undergoing the Ross procedure. Mortality rates at 1, 5, and 10 years, respectively, was 2.8%, 2.8%, and 4.4% in the first cohort and 0%, 0%, and 0% in the second cohort.…”
Section: Ross Procedure-the Revival Of Interest In An Old Procedures ...mentioning
confidence: 99%
“…Romeo et al 58 conducted a multicentric cohort including 1431 patients with a median age of 48.5 years. The in‐hospital mortality rate was 0.7%.…”
Section: Ross Procedure—the Revival Of Interest In An Old Procedures ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Female sex was significantly associated with lower gradients of homografts, but also increased the likelihood of significant regurgitation. In contrast, the use of homografts rather than bioprosthesis and older donor age was associated with a lower likelihood of significant regurgitation ( 39 ). Another study showed that age and homograft diameter at the time of operation was also associated with valve function ( 40 ).…”
Section: Clinical Application Of Homograft Valved Conduitmentioning
confidence: 99%
“…Freedom from autograft and homograft intervention was 92 and 97%, respectively, during that time. 26…”
Section: Introductionmentioning
confidence: 99%